Pusat Olahraga Rekreasi Menembak di Provinsi Gorontalo dengan Pendekatan Arsitektur Modern Kontemporer - Alif Firmansyah D. Kaili; Lydia Surijani Tatura; Syafriyani (Transbahasa, 2026)
Gorontalo Province holds significant potential for the development of sports tourism, particularly in shooting sports. However, the region lacks a representative facility that meets national standards in terms of safety, comfort, and design. This issue underlines the urgency of designing a Shooting Sports Tourism Center that accommodates the needs of both athletes and tourists. The main objectives of this design are to create a safe and comfortable shooting facility that complies with national building standards and to implement a modern contemporary architectural approach that reflects current design trends. This study employs a descriptive qualitative method with a participatory observation approach, involving data collection, presentation, compilation, and analysis as the basis for formulating the planning and design concepts. The resulting design concept integrates functional, aesthetic, and contextual aspects, featuring well-organized zoning for training areas, competition spaces, supporting facilities, and public spaces. This project is expected to serve as a new landmark in Gorontalo and to contribute to the growth of sports tourism in the region.